(3GdUMGaI GdfSGFjI aj GdhWf GdYQHj (B/s - (3EHQGgje, ESeGYjds ((3GdbGgQI (B:s (3GdOGQ GdOhdjI ddfTQ h GdJhRjY ,s, 1996)
(3GdcJGH GdeQLY GdGhd aj GddZI GdYQHjI GdPj jDQN dfTCI h JWhQ GdUMGaI GdfSGFjI aj GdhWf GdYQHj efP Gf GUOQJ (B3(3gfO fhad(B3 (3Ghd eLdI fSGFjI YQHjI h gj eLdI (B3 (3GdaJGI(B3 (3HGdGScfOQjI aj (B20 (3fhaeHQ (B1892 (3h MJi fgGjI YGe(B1994s
Keywords: (3GdUMGaIs; (3GdUMGaI GdfSGFjIs; (3GdhWf GdYQHjs